Educational experiences: voices of incarcerated male youth - Singleton, Everett B., author; Davies, Timothy, advisor; Makela, Carole, committee member; Quick, Don, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2016)
Youth who experience academic failure are at a greater risk for evolvement in delinquency. Their perceptions regarding educational experiences could reveal some of their challenges or barriers to academic achievement. The purpose of this research project was to understand how incarcerated male youth perceive their educational experiences, and to understand the prevailing themes and commonalities in their stories. A phenomenological approach was used to describe the participants' educational and lived experiences. One all male juvenile correctional facility in a Southern state was selected for this case study research. The structure is designed to contain youth who have committed at least three or more felonies and remanded by the courts for treatment. Fifteen incarcerated youth, aged 18, were interviewed and provided knowledge and insight into the research questions. Each was assigned pseudonyms to preserve anonymity. Interviews were conducted face to face, recorded, and then transcribed. The themes that emerged from the interviews include: (1) conflicted interpersonal relationships; (2) educational disconnect; and (3) personal demons, all of which impacted their academic journey. Participants were also asked about their earliest educational outlook, as well as their future outlook, as it relates to short- and long-term goals. Their individual and collective responses painted a picture of the factors that led to their academic challenges, criminal behavior and incarceration. Results for this study indicated that some incarcerated youth make meaning of their educational experiences through a series of complex events, changes and circumstances occurring in their school and personal lives. Some of these relationships were positive iii connections that supported and propelled them forward, while conflicting relationships were damaging and often exposed them to unhealthy environments, substance abuse and criminal elements. Although their experiences varied, it was clear that failure was an ongoing occurrence throughout their academic journey. While for some, the educational disconnect was internal to the school environment; for others, disruptions in their home lives interfered with their ability to maintain regular attendance and remain focused on their studies. Issues with suspensions, expulsion, truancy, retention, academic failure, school violence, poverty and parental neglect seemed pervasive throughout their stories; and some shared feelings of inferiority due to their current academic shortcomings. Participants revealed personal demons that were defined as dark moments in their lives and had a direct or indirect impact on their academic journey. These were traumatic events, unforeseen and unexpected circumstances occurring in their family, school and community lives. They shared information regarding their earliest educational outlook, which for some seemed positive and provided an opportunity to grow academically and personally, while others experienced adversity and negative outcomes early on.